Effects of Rosiglitazone and Acarbose (with and without Cornstarch Diet) on Serum Electrolytes in Diabetic Rats - Humera Khatoon and Rahila Najam (Journal of Applied Pharmaceutical Science)
The purpose of this study is to highlight potential risks associated with the use of oral hypoglycemics as monotherapy in treatment of type 2 diabetes mellitus. For this study 40 Wistar albino rats were equally divided into four groups. Group I served as diabetic control and II, III and IV were treated with acarbose with regular diet, acarbose with cooked cornstarch diet and rosiglitazone respectively. Diabetes was induced with a single dose of alloxan monohydrate IP at a dose of 150 mg/kg body weight. Drug samples were administered orally for a period of 4 weeks and effects of the drugs were studied on day 7, 15 and 30 for serum level of sodium and potassium. Results showed decrease in sodium and potassium level in all treated groups on day 7. On day 30 levels were increased in group II and IV but decreased significantly in group III. It has been concluded that chronic doses of rosiglitazone and acarbose with regular diet may cause abnormal levels of electrolytes which may cause irregular cardiac contractility. Administration of acarbose with cornstarch diet may be beneficial in regulating cardiac contractility.
Keywords: Resistant starch, oral hypoglycemic, cardiac toxicity, serum electrolytes, nephrotoxicity, alpha-glucosidase inhibitor.